2017
DOI: 10.1186/s12981-017-0145-z
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL outcomes and loss to follow-up among people living with HIV participating in the NAMWEZA intervention in Dar es Salaam, Tanzania: a prospective cohort study

Abstract: Background: Psychosocial factors have been linked with loss to follow-up (LTFU) and clinical outcomes among people living with HIV (PLH), however little is known about the effect of psychosocial support on LTFU among PLH in treatment and care. The purpose of this study was to explore the effect of NAMWEZA ("Yes, together we can") friends' psychosocial support intervention on clinical outcomes and LTFU among PLH. NAMWEZA is based on a novel program using "appreciative inquiry", positive psychology approaches to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 26 publications
6
23
1
1
Order By: Relevance
“…Retention in care (ie, repeat utilisation) is a frequently used measure of health system quality for conditions that require a course of continuous care, such as HIV and non-communicable diseases as well as immunisation. 21 , 22 , 23 Because condition-specific utilisation measures were not available for all 61 conditions in LMICs, we used population utilisation data for conditions with similar clinical features and level of acuity. 24 For conditions such as neonatal HIV and vaccine preventable diseases, the health system can prevent all incidental cases when people seek preventive care.…”
Section: Methodsmentioning
confidence: 99%
“…Retention in care (ie, repeat utilisation) is a frequently used measure of health system quality for conditions that require a course of continuous care, such as HIV and non-communicable diseases as well as immunisation. 21 , 22 , 23 Because condition-specific utilisation measures were not available for all 61 conditions in LMICs, we used population utilisation data for conditions with similar clinical features and level of acuity. 24 For conditions such as neonatal HIV and vaccine preventable diseases, the health system can prevent all incidental cases when people seek preventive care.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, Network Members who were living with HIV demonstrated an increase in access to HIV treatment. Although examining clinical outcomes was beyond the scope of this trial, an observational study comparing people living with HIV in NAMWEZA with those who did not participate demonstrated an increase in weight and greater treatment retention at follow-up among those in the programme 56. This finding supports a fundamental goal of the NAMWEZA programme— to improve the overall health and well-being of people living with HIV, which in turn strengthens their capacity to serve as Change Agents in their communities.…”
Section: Resultsmentioning
confidence: 58%
“…The PST component includes six psychosocial group therapy sessions plus one orientation session prior to delivery. Implementation strategies for the PST sessions are borrowed from NAMWEZA [36], a participatory and strengths-based program that was adapted for an urban Tanzanian context and demonstrated improved clinical outcomes in PLH [37]. This approach promotes awareness of one's own strengths and assertive communication skills.…”
Section: Intervention and Control Conditionsmentioning
confidence: 99%